2008
DOI: 10.1164/rccm.200702-333oc
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Specific Gene Expression Profiling in Multiple Models of Lung Disease

Abstract: Rationale: Microarray technology is widely employed for studying the molecular mechanisms underlying complex diseases. However, analyses of individual diseases or models of diseases frequently yield extensive lists of differentially expressed genes with uncertain relationships to disease pathogenesis. Objectives: To compare gene expression changes in a heterogeneous set of lung disease models in order to identify common gene expression changes seen in diverse forms of lung pathology, as well as relatively smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 61 publications
8
74
0
Order By: Relevance
“…The well-characterized model of bleomycin-induced lung injury has been extensively used to investigate potential pathways involved in the pathogenesis of pulmonary fibrosis and to explore therapeutic approaches (22). Despite some limitations with regard to recapitulation of human disease, a number of pathways that are up-regulated in IPF (e.g., TGF-β and Wnt/β-catenin) are also up-regulated following bleomycin (28). As reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…The well-characterized model of bleomycin-induced lung injury has been extensively used to investigate potential pathways involved in the pathogenesis of pulmonary fibrosis and to explore therapeutic approaches (22). Despite some limitations with regard to recapitulation of human disease, a number of pathways that are up-regulated in IPF (e.g., TGF-β and Wnt/β-catenin) are also up-regulated following bleomycin (28). As reviewed in ref.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation has been suggested to have a very limited involvement in the pathogenesis of pulmonary fibrosis (Mapel et al 1996;Selman et al 2001), and the role of Wnt signaling in lung inflammation has largely been unexplored. Based on a comparison of the gene expression profiles in different mouse models of infection, allergy, and lung injury, Lewis et al (2008) found the regulation of the Wnt signaling pathway in only one mouse model of bleomycin-induced lung fibrosis, and not in any other inflammatory lung disease model (Lewis et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs may play an important role in asthma as it is characterized by marked changes in gene and protein expression in the lung. 68,69 By using three different experimental animal models of asthma viz, OVA (ovalbumin), Aspergillus fumigatus, lung specific-IL-13 overexpression, Lu et al 70 have shown that IL-12p35 (a component of IL-12) expression is downregulated during asthma, which is correlated with increased expression of miR-21. Subsequent analyses have shown that miR-21 was primarily detected in the cytoplasm of mononuclear expression of miR-21 under Nestin (a protein marker for neural stem cells, also expressed in adult haematopoietic cells) promoter control.…”
Section: Role Of Mir-21 In Developmentmentioning
confidence: 99%